2012
DOI: 10.1115/1.4004074
|View full text |Cite
|
Sign up to set email alerts
|

Ion Current, Combustion and Emission Characteristics in an Automotive Common Rail Diesel Engine

Abstract: Ion Current, Combustion and Emission Characteristics in an Automotive Common Raii Diesel EngineAdvanced electronically controlled diesel engines require a feedback signal to the ECU to adjust different operating parameters and meet demands for power, better fuel economy and low emissions. Different types of in-cylinder combustion sensors are being considered to produce this signal. This paper presents results of an experimental investigation on the characteristics of the ion current in an automotive diesel eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Ion sensors such as these necessarily measure the concentration of ions only in the proximity of the sensor. 18 Head gasket ion sensors have been shown to produce more global results 3 but are more difficult to manufacture and install. Four locations for the ion sensor were tested by Kubach et al, 1 and the best signal was found to come from the sensor installed in the glow-plug port of the cylinder head.…”
Section: Methodsmentioning
confidence: 99%
“…Ion sensors such as these necessarily measure the concentration of ions only in the proximity of the sensor. 18 Head gasket ion sensors have been shown to produce more global results 3 but are more difficult to manufacture and install. Four locations for the ion sensor were tested by Kubach et al, 1 and the best signal was found to come from the sensor installed in the glow-plug port of the cylinder head.…”
Section: Methodsmentioning
confidence: 99%
“…In the ion sensing system, a spark plug is used as the ion current sensor, and a 200 V DC power source is exerted to supply the electric field. The details of this system can be seen in [11,18,30] .…”
Section: Engine Testing and Ion Sensing Systemmentioning
confidence: 98%
“…Recently, several technical solutions including ionic sensor location optimization [11] , alkali metal based ionization enhancement additives [12] and high frequency AC power source [13] , are proposed for improvement of the ion current sensing system. Optimization of any of these proposals will be strongly aided by a chemical kinetic simulation of the in-cylinder flame ionization process.…”
Section: Introductionmentioning
confidence: 99%
“…This is not the case in diesel engines where different types of flames are produced from the combustion of the heterogeneous charge developed from the fuel sprays injected inside the cylinder [1,2]. Due to the complexity of diesel combustion, only a few publications that deal with ionization appear in the literature [2,[3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%